Production and Purification of Phosphatidylinositol Mannosides from Mycobacterium smegmatis Biomass. Issue 6 (27th June 2022) - Nobre, Rodrigo N.; Esteves, Ana M.; Borges, Nuno; Rebelo, Sara; Liu, Yaqi; Mancia, Filippo; Santos, Helena
Abstract: Mycobacterium tuberculosis, the etiological agent of tuberculosis, is regarded as the most successful pathogen of humankind and a major threat to global health. The mycobacterial cell wall is vital for cell growth, virulence, and resistance to antibiotics, and thus constitutes a unique target for drug development. To characterize the enzymes catalyzing the synthesis of the cell wall components, considerable amounts of substrates are required. Since many mycobacterial cell wall lipids, particularly phosphatidylinositol mannosides (PIMs), are not commercially available, isolation from cell biomass is the most straightforward way to obtain these compounds. In this study, we optimized a protocol to extract and purify PIM species, in particular Ac1 PIM2 and Ac1 PIM4, which can be further used for the identification and characterization of target enzymes. PIMs were extracted from Mycobacterium smegmatis mc 2 155 ΔPimE using organic solvents, and purified through three consecutive chromatography steps. Thin‐layer chromatography (TLC) was used in‐between purification steps to evaluate the success of lipid separation, and nuclear magnetic resonance (NMR) was used for product quantification and to assess purity. Typically, from a 60 g batch of M. smegmatis biomass we were able to isolate approximately 9 mg of Ac1 PIM2 and 1.8 mg of Ac1 PIM4 . This is the first time the purification of phosphatidylinositol tetramannoside has been reported. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Growth of M. smegmatis mc 2 155 ∆PimE Basic Protocol 2 : Extraction of lipids from M. smegmatis mc 2 155 ∆PimE Basic Protocol 3 : Treatment of the lipid extract for isolation of phospholipids Basic Protocol 4 : Isolation of phosphatidylinositol mannosides Basic Protocol 5 : Quantification of phosphatidylinositol mannosides